What 15 the role of corporate governance as a subspecies of corporate law in the level of corporate risk taking? - Zsa-zsa Becker, Cleo Roxanne (Centre for Law and Society, 2026)
Following the major corporate collapses of the past decade, companies around the world have been considering whether these collapses are a result of the failure of directors of corporations to curb their appetites for excessive risk taking. A director's duty to promote the success of the company places great pressure on directors to maximise profits in the short term. In addition to shareholder pressure directors are tempted with huge bonuses and remuneration packages for producing short term profits. This paper will examine how corporate governance as a sub-species of corporate Jaw can work effectively with regulation to prevent and discourage excessive risk taking behaviour.